The Impact of Green HRM on Employees’ Eco-Friendly Behavior: The Mediator Role of Organizational Identification - Ribeiro, Neuza (2022)
This study sought to explore the impact of green human resource management on organizational identification and employees’ eco-friendly behavior, as well as the mediating role of organizational identification in the relationship between green human resource management and employees’ eco-friendly behavior. To achieve the study objectives, a cross-sectional quantitative study was developed, for which the data were obtained through a structured questionnaire containing the measures of the study variables. Data were collected from 235 employees from several Portuguese tourism organizations participating in the study. The Harman test and bootstrapping were applied previously to the assessment of the results. The mediation study’s hypothesis was evaluated using Baron and Kenny’s linear regression method, and subsequently complemented using the Sobel test. The findings showed that the implementation of green HRM practices in tourism organizations has a positive impact on employees’ eco-friendly behavior and on organizational identification, with the latter mediating the relationship between green human resource management and employees’ eco-friendly behavior. The study is breaking new ground because it incorporates the impact of green human resource management on organizational identification and employees’ eco-friendly behavior in a single research model, thus expanding knowledge on the subject, namely in the tourism sector in Portugal